Antimicrobial Resistance in Salmonella enterica Serovar Typhi Isolates from Bangladesh, Indonesia, Taiwan, and Vietnam - Chiou, Chien-Shun (Antimicrob Agents Chemother, 2014)
We characterized Salmonella enterica serovar Typhi isolates from Bangladesh, Indonesia, Taiwan, and Vietnam to investigate their genetic relatedness and antimicrobial resistance. The isolates from Bangladesh and Vietnam were genetically closely related but were distant from those from Indonesia and Taiwan. All but a few isolates from Indonesia and Taiwan were susceptible to all antimicrobials tested. The majority of isolates from Bangladesh and Vietnam were multidrug resistant (MDR) and belonged to the widespread haplotype H58 clone. IncHI1 plasmids were detected in all MDR S. Typhi isolates from Vietnam but in only 15% of MDR isolates from Bangladesh. Resistance genes in the majority of MDR S. Typhi isolates from Bangladesh should reside in the chromosome. Among the isolates from Bangladesh, 82% and 40% were resistant to various concentrations of nalidixic acid and ciprofloxacin, respectively. Several resistance mechanisms, including alterations in gyrase A, the presence of QnrS, and enhanced efflux pumps, were involved in the reduced susceptibility and resistance to fluoroquinolones. Intensive surveillance is necessary to monitor the spread of chromosome-mediated MDR and fluoroquinolone-resistant S. Typhi emerging in Bangladesh.